2022
DOI: 10.1007/s00436-022-07527-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of Cryptosporidium species from domestic ruminants and wild reptiles in Cyprus

Abstract: The presence of Cryptosporidium species in faecal samples of 32 sheep ( Aries bovis ), 10 goats ( Capra circus ), 1 blunt nose viper ( Macrovipera lebetina lebetina ), 3 Kotschy’s geckos ( Mediodactylus kotschyi ) and 6 wild stellagamas ( Stellagama stellio cypriaca ) in Cyprus were investigated by polymerase chain reaction (PCR) and sequencing. Cryptosporidium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The species identified were C. bovis , C. ryanae and C. parvum . Similarly, Schou et al [ 5 ] reported a high occurrence of Cryptosporidium in domestic sheep (9/32 = 28%) and goats (5/10 = 50%) at local farms, although the number of samples investigated was low. The species identified were C. xiaoi and C. ubiquitum in sheep and C. parvum in goats.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The species identified were C. bovis , C. ryanae and C. parvum . Similarly, Schou et al [ 5 ] reported a high occurrence of Cryptosporidium in domestic sheep (9/32 = 28%) and goats (5/10 = 50%) at local farms, although the number of samples investigated was low. The species identified were C. xiaoi and C. ubiquitum in sheep and C. parvum in goats.…”
Section: Discussionmentioning
confidence: 95%
“…The Cryptosporidium parvum sequences that were analysed from animals isolated in Cyprus (Schou et al . [ 5 ]) are marked with a solid square …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations